TREM2, Driving the Microglial Polarization, Has a TLR4 Sensitivity Profile After Subarachnoid Hemorrhage - Hu, Yangchun; Li, Chao; Wang, Xiaojian; Chen, Weiwei; Qian, Yu; Dai, Xingliang (Frontiers in Cell and Developmental Biology, 2021)
Abstract Increasing evidence suggests that triggering receptor expressed on myeloid cells 2 (TREM2) is implicated in the pathophysiology of neuroinflammation. The aim here was to investigate the neuroprotective role of TREM2 and its regulatory mechanism after subarachnoid hemorrhage (SAH). TREM2 siRNA was administered to measure the detrimental role of TREM2 in mediating microglial polarization in vivo and in vitro after experimental SAH. The relationship between Toll-like receptor 4 (TLR4) signaling and TREM2 was further explored. The soluble TREM2 from the cerebrospinal fluid (CSF) of patients with SAH was detected. The results showed that TREM2 mainly located in the microglia and presented a markedly delayed elevation after SAH. TREM2 knockdown triggered increased pro-inflammatory productions, aggravated microglial activities, and further exacerbated neurological dysfunction after SAH. Significantly, TLR4 knockout increased the expression of TREM2, accompanied by ameliorated neuroinflammation and improved neurological function. Corresponding with different clinical Hunt-Hess grades, obviously enhanced accumulations of soluble TREM2 were detected in the CSF of patients with SAH. TREM2 played a pivotal role in mediating microglial polarization after SAH, and the neuroprotective effect of TREM2 might be potentially suppressed by the hyperactive TLR4 in the early phase of SAH. Pharmacological targeting of TREM2 may be a promising strategy for SAH therapy.